2013
DOI: 10.1002/jcb.24553
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA inhibits breast cancer stem cells growth in vitro and in vivo through attenuation of IL‐6/STAT3/NF‐kB signaling pathways

Abstract: Cancer stem cells (CSCs) are maintained by inflammatory cytokines and signaling pathways. Tanshinone IIA (Tan-IIA) possesses anti-cancer and anti-inflammatory activities. The purpose of this study is to confirm the growth inhibition effect of Tan-IIA on human breast CSCs growth in vitro and in vivo and to explore the possible mechanism of its activity. Human breast CSCs were enriched and expanded under serum-free mammosphere culture condition, and identified through mammosphere formation, toluidine blue staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
58
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 46 publications
2
58
0
Order By: Relevance
“…In this study, we found that TSIIA decreased significantly the cell viability of EESCs in a dose-dependent manner, and 20 lL of TSIIA could result in obviously decreased cell viability; this is similar to recent observations that TSIIA could inhibit multiple cancer cells proliferation [20,36,37]. Furthermore, overexpression of 14-3-3f could restore cell viability of TSIIA-treated EESCs, implying that the inhibitory effect of cell viability was mediated by 14-3-3f.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we found that TSIIA decreased significantly the cell viability of EESCs in a dose-dependent manner, and 20 lL of TSIIA could result in obviously decreased cell viability; this is similar to recent observations that TSIIA could inhibit multiple cancer cells proliferation [20,36,37]. Furthermore, overexpression of 14-3-3f could restore cell viability of TSIIA-treated EESCs, implying that the inhibitory effect of cell viability was mediated by 14-3-3f.…”
Section: Discussionsupporting
confidence: 89%
“…Tan IIA activated the c-Jun N-terminal protein kinase (JNK) pathway in chronic myeloid leukemia cells (25) as well as the IL-6/STAT3/NF-κB signaling pathways in breast cancer cells (22); therefore, these pathways will be assessed in breast cancer cells in future studies. In addition, although the effect of Tan IIA on EMT markers is suggestive of inhibition of migration, further analyses will specifically assess the effects of Tan IIA on cell migration in vitro and metastasis in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the in vitro and in vivo growth inhibitory effects of Tan IIA on leukemia cells (15), prostate cancer cells (16), colon cancer cells (17), pancreatic cancer cells (18), hepatocellular carcinoma (19), gastric cancer cells (20), cervical cancer cells (21), and breast cancer cells (22), the effects of Tan IIA on hypoxia-induced DOX resistance were analyzed in two breast cancer cell lines. Tan IIA increased the sensitivity of both MCF-1 and HCC1937 cells cultured in hypoxia to DOX in part through HIF-1α.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we demonstrated that sesamin reduced the SP cells fraction and viability in a dose-dependent manner. Two explanations, either elimination [27,28] or differentiation [29,30] of SP cells may account for this phenomenon. The majority of the SP cells (more than 83%) were viable at this situation (after treatment with sesamin), however, as determined by trypan blue exclusion (data not shown).…”
Section: Discussionmentioning
confidence: 99%